Masih Relevankah Konsep Matematika Dikolaborasikan Dengan Aquaponik Hingga Menjadi Mathematic Aquaponik - Alayubi, Sholahudin; Siskawati, Fury Styo; Sri Wahyuni, Endang (LPPM Universitas Hasyim Asy'ari Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Starting from the assumption that mathematics is identical to calculating numbers, complicated formulas, working on questions that are difficult to understand, making mathematics uninteresting to the point of having an impact on the low mastery of mathematics in students not only at the higher education level but also secondary education feels the same thing. This situation inspired researchers to change students' thinking patterns so that they consider mathematics not only about calculating numbers but more about unique learning that is definitely used and useful in everyday life so that it is fun to learn. This study aims to describe the collaboration of mathematical concepts with aquaponics to become mathematical aquaponics which can later be used in mathematics learning. This type of research is descriptive with a qualitative approach. The data collection method used is documentation with the data analysis method using literature study. Furthermore, the results obtained from this study indicate that mathematics is still quite relevant if collaborated with aquaponics to become mathematical aquaponics. Furthermore, mathematical aquaponics are worthy of being developed as an innovative mathematics learning medium in the future. Then, for the suggestions that can be conveyed, through this research, mathematics should be collaborated with various disciplines so that it does not only focus on calculations and numbers which are considered boring for most students, so that later mathematics will feel fun and be liked by many people.